eIF5A: Uma proteína essencial para a viabilidade celular cuja função permanece obscura - Frigieri, M. C. [UNESP]; Cano, V. S P [UNESP]; Apponi, L. H. [UNESP]; Dias, C. A O [UNESP]; Gregio, A. P B [UNESP]; João-Luiz, M. V S [UNESP]; Silveira, W. S. [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP] (My University, 2006)
The putative translation initiation factor 5A (eIF5A) is a highly abundant and conserved protein in all eukaryotes and archaebacteria. This factor is essential for cell viability and is the only cellular protein known to contain the unusual amino acid residue hypusine. In Saccharomyces cerevisiae eIF5A is expressed in aerobic conditions by the gene TIF51A. Although eIF5A has been known for almost 30 years, the biological role of this protein is still obscure. This article reviews the research on the function of eIF5A, discussing the evidence for its involvement in various steps of mRNA metabolism, including translation initiation, nucleocytoplasmic transport and mRNA decay. Moreover, it indicates other studies that have associated eIF5A with cell proliferation and cell cycle progression. Finally, this review presents recent results obtained in our laboratory that reemphasize the role of eIF5A in the translation scenario. Further experiments will be necessary to define the role played by eIF5A in the translational machinery.

O provável fator de início de tradução 5A (eIF5A) é uma proteína abundante e altamente conservada em todos os organismos eucarióticos observados e também está presente em arquebactérias. eIF5A é essencial para a viabilidade celular e esse fator é a única proteína descrita que contém o resíduo de aminoácido hipusina. Em Saccharomyces cerevisiae, eIF5A é expressa em condições aeróbicas pelo gene TIF51A. Apesar de eIF5A ser conhecida há quase 30 anos, a sua função biológica ainda é obscura. Este artigo revisa os estudos de caracterização funcional de eIF5A, evidenciando como esse fator foi envolvido com diferentes etapas do metabolismo de RNA mensageiro (mRNA), como o início de tradução, o transporte nucleocitoplasmático e o decaimento de RNA mensageiro. Ainda, estudos que evidenciaram o envolvimento de eIF5A com a proliferação celular e progressão no ciclo celular também foram abordados. Finalmente, esse artigo apresenta os resultados recentes dos experimentos que colocam eIF5A novamente no cenário da tradução. Novos experimentos serão necessários para definir o papel desempenhado por eIF5A na maquinaria de tradução.
eIF5A: An essential protein for cell viability whose function remains obscure
Keywords: Cell proliferation; eIF5A; Hypusine; Protein synthesis; Translation; initiation factor; messenger RNA; translation initiation factor 5a; unclassified drug; cell cycle progression; cell proliferation; cell viability; nucleocytoplasmic transport; protein function; review; RNA metabolism; RNA translation